2005
DOI: 10.1007/s10549-005-9105-8
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk factors and mammographic breast density in women over age 70

Abstract: Factors associated with breast density in older, post-menopausal women differ from traditional breast cancer risk factors and from factors associated with breast density in pre-menopausal and younger post-menopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
28
2
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 61 publications
9
28
2
1
Order By: Relevance
“…Our main finding for reduced percent density with greater number of births support most previous findings [12,16,17,35,36]. In our data, this association was most pronounced among thinner women, although the interaction term for number of births and BMI was not statistically significant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our main finding for reduced percent density with greater number of births support most previous findings [12,16,17,35,36]. In our data, this association was most pronounced among thinner women, although the interaction term for number of births and BMI was not statistically significant.…”
Section: Discussionsupporting
confidence: 91%
“…A similar trend was observed in a previous study evaluating reproductive factors in relation to dense and non-dense breast area, with the hypothesis that factors associated with dense breast area were more etiologically relevant [35]. Most previous studies reported no association between age at menarche and percent density [12,[15][16][17]35,36].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…14 The predicted age at which density ceased to decline was 65 years, at the upper limit of the included age range, broadly in agreement with data from 2 other studies. 2,15 We found that mean levels of breast density are affected by both immediate and distal factors, but that its rate of change at ages 50-65 years is affected only by immediate factors, i.e., use of HT and menopause. Credibility of these findings are supported by their striking similarity with those from the Minnesota Breast Cancer Family Study.…”
Section: Epidemiology 458mentioning
confidence: 87%
“…PIH has been fairly consistently associated with a reduction in breast cancer risk (e.g., [5, 21]), though some studies have found no (e.g., [6, 22]) or even increased risk [23, 24]. PIH is a multifactorial disease with genetic and environmental factors known to be involved in its etiology although full understanding of its pathogenesis remains elusive despite decades of research [25]. Likewise, the mechanism by which PIH affects breast cancer risk is unknown although potentially via the same etiologic basis as PIH, with theories focusing on placental dysfunction and a subsequent lowering of circulating estrogens [26], increase in serum insulin-like growth factor [27], and/or angiogenic factors [28].…”
Section: Discussionmentioning
confidence: 99%